58.8k views
4 votes
3(x+1)-2x=-6
Slove this

User Animesh D
by
4.9k points

1 Answer

2 votes

Answer:

x = -9

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

3(x + 1) - 2x = -6

Step 2: Solve for x

  1. Distribute 3: 3x + 3 - 2x = -6
  2. Combine like terms: x + 3 = -6
  3. Isolate x: x = -9

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 3(-9 + 1) - 2(-9) = -6
  2. Add: 3(-8) - 2(-9) = -6
  3. Multiply: -24 + 18 = -6
  4. Add: -6 = -6

Here we see that -6 does indeed equal -6.

∴ x = -9 is the solution to the equation.

User Roman Akash
by
5.6k points